The Influence of Work Motivation and Discipline on the Performance of Social Studies Teachers in JHS in Bireuen Regency - Zahara, Zahara; Chairani, Mira; Akbar, Aidil; Syamra, Yesmira; Agustina, Yenni (Postgraduate School, Universitas Negeri Padang, 2024)
This study was motivated by findings on the implementation of the